2004
DOI: 10.1097/01.asn.0000100125.21491.46
|View full text |Cite
|
Sign up to set email alerts
|

The Number, Quality, and Coverage of Randomized Controlled Trials in Nephrology

Abstract: Abstract. Randomized controlled trials (RCT) are the optimal study design to answer intervention questions. The authors evaluated the number, quality, and coverage of RCT in nephrology. MEDLINE was searched using the relevant medical subject headings for nephrology and 12 major specialties in internal medicine, limited by "randomized controlled trial" as a publication type. A random selection of 160 RCT in nephrology (40 for each decade) published since 1966 and an additional 270 RCT from ongoing or published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
200
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(206 citation statements)
references
References 32 publications
2
200
0
3
Order By: Relevance
“…Herein lies a major problem in the field of kidney disease: The lack of high quality evidence on which to base our practice in nephrology. This was underlined by Strippoli et al (13), who demonstrated exactly where we sit as a specialty on the randomized, controlled trials (RCTs) ladder in an article in JASN in 2004 (the bottom rung). Figure 2 details the number of articles in PubMed published on human kidney disease in the past 18 yr, split into three 6-yr time periods.…”
Section: Guideline Development Methodsmentioning
confidence: 99%
“…Herein lies a major problem in the field of kidney disease: The lack of high quality evidence on which to base our practice in nephrology. This was underlined by Strippoli et al (13), who demonstrated exactly where we sit as a specialty on the randomized, controlled trials (RCTs) ladder in an article in JASN in 2004 (the bottom rung). Figure 2 details the number of articles in PubMed published on human kidney disease in the past 18 yr, split into three 6-yr time periods.…”
Section: Guideline Development Methodsmentioning
confidence: 99%
“…The standard of evidence forming the basis for current clinical practice guidelines in the care of dialysis patients is derived largely from epidemiologic studies and not from randomized clinical trials. There are a paucity of randomized clinical trials in the dialysis population demonstrating that any process of care is associated with an improved outcome (18). Notably, the HEMO Study, the most comprehensive clinical trial performed to date in the hemodialysis population, supported the null hypothesis for the interventions (dose of dialysis and dialysis membrane flux) on primary outcomes, despite robust epidemiologic data suggesting that these process variables would be related to patient outcomes (19).…”
Section: Potential Pitfalls In Paying For Quality In Esrdmentioning
confidence: 96%
“…The quality of the papers was out of the scope of this study. The quality of papers becomes an important and attractive topic while evaluating the characteristics of publications (5)(6)(7)(8). Further evaluations are required for assessing the quality of papers of rheumatologists.…”
Section: Discussionmentioning
confidence: 99%